Diferença e sensibilidade em Gilles Deleuze - Joao Gabriel Alves Domingos (2010)
We approached the problem of the art in the Deleuze philosophy by a contextualization of sensibility inside a project of thinking the difference. In the introduction, we approached the procedure utilized by Deleuze to make his history of philosophy. After this first moment, we show how, by his lecture of the method of division from the Platonic dialogues (Statesman, Sophist, Phaedrus), Deleuze developed a critique of analogy, because the critique is a way to correspond the thought with the representation, leaving the difference unthinkable. In the second part, we read Kant, showing how his doctrine of the faculties 2 also realize an image of thought as representation. But, in both cases, the Deleuze's interpretations are ambiguous. He found, in these representational systems, the moments in which the difference is thought. In Plato, when he proposes the adventure of thinking the not-being in the Sophist (indicating himself what's mean the Niezschean expression to reverse Platonism). In Kant, (1) in the Critique of Pure Reason when he puts a third element (the pure form of time) into the logic of two terms of Cartesian cogito and, (2) in Critique of Judgment, where the sublime is capable of carrying the faculties to their respective limits, producing contingent harmonies (that is, not presupposed) among them. According to Deleuze, the theory of conditions is left to the assumption of the perspective of genesis; the conditions of possibilities is left to assume of the conditions of real experience. The notion of repetition found in the Nietzsche's eternal return as intensive repetition of difference is crucial for this genetic perspective, because this concept expresses a logic in which there's no appeal to any transcendence.